: Gestión pedagógica en el aula: “Clima social escolar, desde la percepción de los estudiantes y profesores del séptimo año de educación básica de los centros educativos Afraser Fe y Alegría; Instituto Educativo Particular Pío XII, de la ciudad de Quito, cantón Quito, provincia de Pichincha, 2011 – 2012. - Legña Casanova, Martha Silvana (2013)
This investigative work is based upon the importance that achieving quality education currently has; that is to say the student is capable of learning in a significant way and is the designer of his own knowledge in collaboration with his classmates or under the guidance of his teacher. Based upon this new educational model, the biographical investigation and field investigation upon educational teaching administration in classroom, on Pedagogical management in the Classroom, School Social Climate: From The perception of students and teachers in the seventh year of basic education in the educational centers, Afraser “Fe y Alegría” e Instituto Educativo Particular “Pio XII”, of the city of Quito, made possible the realization of a proposal to solve problems found in both centers. After study and analysis, The lack of implementation of Active Learning Techniques in the Classroom, in this way forms of evaluation become essential in order to arrive at the objective: a quality education, the reason for which the presented proposal is oriented to satisfy institutional necessities of teachers and at the same time will concentrate on the need to develop and carry out their pedagogical competencies and optimize its management the classroom